2022
DOI: 10.3390/ijerph19052707
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Factors to COVID-19 Vaccine Adoption in Gujarat, India

Abstract: The COVID-19 pandemic has posed threats to human life across the globe, including India. Vaccinating is an effective means of addressing the pandemic threat. The government of India has implemented a massive vaccination drive to save its citizens from the deadly virus. However, the effort has faced multiple challenges, including vaccine hesitancy. This research understands respondents’ perspectives on factors contributing to the lower vaccination uptake in Gujarat, India. Forty-four semi-structured interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 76 publications
(91 reference statements)
1
17
0
9
Order By: Relevance
“…Three studies found a relationship between likelihood of intention to vaccinate and being male [13][14][15] . One study found that greater vaccine hesitancy was associated with being male 17 , while another found the same association with being female 13 . The other studies did not find any association between vaccine hesitancy and gender.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies found a relationship between likelihood of intention to vaccinate and being male [13][14][15] . One study found that greater vaccine hesitancy was associated with being male 17 , while another found the same association with being female 13 . The other studies did not find any association between vaccine hesitancy and gender.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to political leanings, two studies suggested that left-wing voting could increase the likelihood of accepting the COVID-19 vaccine 13,14 . Furthermore, religious and political leaders and the government had a positive longterm influence on the decision to take the vaccine 17 and trust in health authorities and seeking information on COVID-19 in public media or websites of health authorities also positively influenced vaccination intention 13,18 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of effective COVID-19 vaccines, herd immunity must be achieved by the widespread vaccination of the entire population. In addition to vaccination safety, efficacy, and cost-efficiency, public acceptability is a major factor in determining overall effectiveness [19]. Since the beginning of the vaccination campaign in late 2020, there have been more than 5 billion people fully vaccinated worldwide, accounting for a total of roughly 60% of the global population [20].…”
Section: Introductionmentioning
confidence: 99%